PENGARUH DUKUNGAN SOSIAL, PENGALAMAN KERJA TERHADAP KEPUTUSAN BEKERJA MELALUI SELF EFFICACY - Vishinta Yurnalistie; Hardani Widhiastuti; Rusmalia Dewi (Liberosis: Jurnal Psikologi dan Bimbingan Konseling, 2024)
This research aims to analyze the influence of social support and work experience on the decision to work or not. according to major. The research method used is descriptive quantitative with data analysis using SmartPLS. The population in this study were 47 employees of the CV Mitra Gamesindo Semarang office. This research aims to analyze the influence of social support and work experience on decision making to work outside of your major through self-efficacy. The results of this study show that: 1) social support has a significant effect on decision making to work not according to major, 2) work experience does not significantly influence decision making to work not according to major, 3) social support has a significant effect on decision making to work not according to major through self efficacy, 4) work experience has a significant effect on decision making to work not according to major through self efficacy, 5) social support has a significant effect on self efficacy, 6) work experience has a significant effect on self efficacy and 7) self efficacy has a significant effect on decision making work not according to major.